Scheduling claim analysis: a comprehensive schedule related claims of contract administration for construction industry - Zahidah, Jahidi (2014)
As the construction industry rapidly grows in Malaysia and contributes to our nation’s economic growth, it plays a very important role in the development of our country. The accuracy and completion of the project schedule is important to the early and successful resolution of the schedule delay claim issues. In advance, the causes that contribute to the schedule related claims need to be identified as it will be very helpful in the resolution process from the bottom of the issue. Besides, the adjustment or delay on project schedule that might causes delay claims need to be highlighted by the scheduling practitioners. As this research will study the scheduling claims from the different points of view of project parties (contractors and clients), the questionnaires are extremely critical components as the instrument for this research process. In addition, the data analysis was conducted accordingly from the process of identifying and notifying the contract claims, followed by the determination of the causes of schedule related contract claims and lastly the determination of key elements for a strong schedule related contract claims. The outcomes of this research show that the delays in construction and completion of the contract itself is the main causes that usually lead to a schedule related construction claims. This may due to the incomplete contract, which is the main thing as an agreement in the project. The potential causes to the schedule related contract claims identified in this research are ranked as; 1.Delays in construction and completion of the contract, 2.Incomplete and defective work, and 3.Abnormal or unusual weather conditions. Identify and rank the key elements for a strong schedule related contract claims is the second objective for this research to be conducted. These elements are important in order to obtain a clear and good claim as it is the characteristics that need to be considered and implemented in constructing a schedule related contract claims. The data analyzed find out that the outmost key element that need to be implemented in a strong schedule related contract claims is reviewing and understanding the contract itself in order to determine whether the contract allows for an extension of time and compensation. It means a clear understanding regarding the project’s contract will definitely makes a contract claims stronger. While the other key elements identified are ranked as; 1.Review and understand the contract to determine whether the contract allows for an extension of time and compensation, 2.Notice (either actual or constructive) of the delay must be given, and 3.Determination of the critical path is often required for the calculation of delay damages.